Невідомий малюнок Любеча 1651 р. - Бондар, О.; Волков, М.; Кондратьєв, І. (Сiверянський лiтопис, 2015)
Важливим джерелом з історії урбаністики залишаються зображальні джерела, у
тому числі рисунки придворних художників, архітекторів та військових спеціалістів.
Для історії Лівобережної України ХVII ст. такі джерела є поодинокими, тому запровадження нового або ж переосмислення відомого джерела стає важливою науковою подією. Одним із міст, якому не пощастило із зображальними джерелами, донедавна
був Любеч. У 1651 р., коли місто було захоплено армією Великого князівства Литовського, придворним художником Януша Радзивіла Абрагамом ван Вестерфельдом був зроблений малюнок Любеча. Однак це зображення увійшло в історіографію як вигляд
Лоєва. Атрибуція малюнка шляхом співставлення усіх наявних в нашому розпорядженні
матеріалів дозволяє з упевненістю стверджувати, що на «Łojow oppidum» 1651 р. зображено не Лоєв, а саме Любеч. Важным историческим источником по истории урбанистики являются
изобразительные источники, в том числе рисунки придворных художников, архитекторов и военных специалистов. Для истории Левобережной Украины ХVII в. такие
источники являются достаточно редкими, поэтому введение в исторический оборот
нового источника или переосмысление уже известного стает значимым научным
событием. Одним из городов, которому не повезло с изобразительными источниками, еще недавно был Любеч. В 1651 г., когда город был захвачен армией Великого княжества Литовского, придворным художником Януша Радзивилла Абрахамом ван
Вестерфельдом был сделан рисунок Любеча. Но рисунок вошел в историографию как
рисунок Лоева. Атрибуция рисунка путем сопоставления всех имеющихся в нашем распоряжении материалов позволила с уверенностью утверждать, что на рисунке «Łojow oppidum» 1651 г. изображен именно Любеч, а не Лоев. The attention of the researchers of European urban processes is being increasingly focused
on the study of not only general issues of town structure evolution. They also examine the issues
of reconstruction of topographic and space structure of several towns involving the data
of historical topography, demography and historical public communications. During the late
Middle Ages and the early Modern Period, except for the traditional written evidence and
archeological materials, the researchers got access to a big number of pictorial sources, including
pictures of court painters, architects, and military specialists. There are practically no such
sources for the history of the Left-bank Ukraine that is exactly why the implementation of new
source or re-thinking of the known ones becomes an important event for the national science.
Till nowadays Lyubech was remaining one of the towns of the Northern Left-bank Area
of Ukraine, which did not have luck with pictorial sources of the first half – middle of ХVII
century. Difficult situation in the region significantly influenced that fact, because the town
was the near-border outpost on the border with Tsardom of Muscovy. During 1609-1618 war
Polish-Lithuanian troops’ base was located in Lyubech. In 1612-1613 Lyubech was burnt
away by the army of Muscovy, in 1616 was surrounded by the new fortress. Next year the Muscovy-Tatar army occupied and burnt away only the outskirts of the town. In 1648 Lyubech became one of the key outposts of Hetmanate on the border with the Grand Duchy of
Lithuania, but it was twice occupied by the Lithuanian army in 1649 and 1651. Court artist Abraham van Westerveld was in the circle of the Commander-In-Chief of the Grand Duchy of Lithuania. One of his pictures from German language album «Lithuanian
Campaign of 1651» depicts town of Loyev, but regardless its signature the image does not comply with the topographic structure of Loyev, its famous pictures and descriptions. In particular, there is noncompliance of location of the castle and podil, absence of the Dnieper on the picture; besides the town is depicted as large and not ruined, though it was burnt away in 1648-1649. Mykola Volkav, historian from Belarus’, suggested that the picture is the depiction
of Lyubech town. This suggestion was completely confirmed at further investigations. Comparison of relief, town structure, roads network, etc. were among the basic criteria used in the picture attribution along with the materials of topographic and archeological investigations, and church topography and others.
Thus, the comparison of all available materials gives us possibility to state with certainty that picture «Łojow oppidum», dated 1651, depicts not Loyev, but Lyubech. Nearly two dozens of only direct correspondences, which are confirmed by other sources, indicate that. Further investigation of this picture gives researchers possibility to imagine the town infrastructure, and archeologists will be able to interpret the results of their investigations more accurately.